Women education and development : A new perspective. - Prasad, Janardan; Kaushik, Vijay Kumari (New Delhi : Kanishka Publishers, Distributors, 1995)
Outlines various aspects of different societies in context to women's education. The book provides insights into the future of women's education, so as to understand the importance of women education and development.
Includes bibliographical references and index.
Keywords: Women education; Women in development